Strengthening and Rehabilitation of U-Shaped RC Bridges Using Substitute Cable Ducts - Adam Svoboda; Ladislav Klusáček; Martin Olšák (Advances in Materials Science and Engineering)
The presented paper deals with strengthening and rehabilitation of U-shaped reinforced concrete bridges from the period of 1905–1930 using post-tensioning, which is a suitable, reliable, and durable method. These bridges have two main beams pulled over the bridge deck, which is supported by cross girders. The cross girders connect the two main beams forming a half-frame in the transverse direction, which provides spatial rigidity to the structure. The spans of these bridges are usually between 15 and 25 m. The high efficiency of post-tensioning can be seen on many implemented applications for bridge reconstructions worldwide. However, in this paper, the post-tensioning method is extended by a unique structural system of substitute cable ducts that allows for significantly expanding applicability of this method on existing concrete bridges. This method is highly recommended due to minimization of interventions into the constructions, unseen method of cable arrangement, and hence the absence of impact on appearance, which is appreciated not only in case of valuable historical structures but in general as well. In conclusion, the post-tensioning by monostrands in substitute cable ducts is a highly efficient method for strengthening of existing bridges in order to increase their load-bearing capacities in terms of current traffic load and to extend their service life. This method was also verified by monitoring the behavior of rehabilitated bridges before and after strengthening.